2008
DOI: 10.1177/1558689807312375
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Methods for Full-Strength Results

Abstract: This article discusses the practical application of mixed quantitative and qualitative designs. Mixed methods designs can be especially powerful in illuminating policy solutions and directions for social action, thus supporting the social justice goals of social work and other helping professions. However, the decision to combine methods must be appropriate for the study, elevating the integrity and strength of the results. This article uses two studies of U.S. welfare policy to describe the decisions research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Such is the case in the present study. Analogous to Sosulski and Lawrence's (2008) claim that mixed methods provide for both the how and why phenomena may occur, TCC training stands to enhance the effectiveness of the staff and volunteers in the host TC and, simultaneously, positively enhance their experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Such is the case in the present study. Analogous to Sosulski and Lawrence's (2008) claim that mixed methods provide for both the how and why phenomena may occur, TCC training stands to enhance the effectiveness of the staff and volunteers in the host TC and, simultaneously, positively enhance their experiences.…”
Section: Resultsmentioning
confidence: 99%
“…So, mixed methods studies are often suggested as a way to disentangle intricate relationships and more fully understand complex social phenomena (Sosulski and Lawrence 2008). As a consequence, it was decided to use a combination of methods to tap the strengths of each of data source, and thereby help to improve the validity and reliability of the findings.…”
Section: Methodsmentioning
confidence: 99%
“…After all, the strength of mixed methods presupposes a thoughtfully developed design in which the methods are well integrated (Sosulski & Lawrence, 2008). We accomplished this by having each method designed and implemented based on the insights from preceding findings.…”
Section: Combining Ethnography and New Technology: What Are The Benefmentioning
confidence: 98%